The slope intercept form​: y = -x + 6
In standard form, we have: x + y = 6
Step-by-step explanation:
1) The points: (8,-2)and(12,-6)
The slope intercept formula:
![y\text{ = mx +c}](https://img.qammunity.org/2023/formulas/mathematics/college/lsv9yhrv64gi9ivaiavq77fqqkajuev2ue.png)
where m = slope and c = intercept
m = change in y/ change in x
![\begin{gathered} m\text{ = }((-6-(-2)))/((12-8)) \\ m\text{ = }(-6+2)/(4)\text{ = -4/4} \\ m\text{ = -1} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/tygi5f0hzcnpv615qmhs2ho8d2hw7mulg4.png)
To get the intercept, insert the value of x and y using any of the points:
using point (8, -2) = (x, y)
y = -1x + c
-2 = -(8) + c
-2 = -8 + c
-2+8 = c
c = 6
y = -1(x) + 6
Equation of line with slope -1 and intercept 6
The slope intercept form​: y = -x + 6
2) In standard form: Ax + By = C
In our derived equation, A = -1, B = 1 and c = 6
y + x = 6
x + y = 6
In standard form, we have: x + y = 6